The YellowPress Periodical : #4. - Crombez, Thomas; Dumalin, Caroline; Van Gerrewey, Christophe; Gorus, Kim; Heirwegh, Ward; Loos, Ruth; Van Pelt, Hilde (Antwerp : KdG / St Lucas School of Arts Antwerp, 2017)
Arpaïs Du Bois: Ma belle saison sous le poirier de Vincent ; Elena Op 't Eynde & Dexian Feng: Greta M. ; Saddie Choua: #Episode 3-I swear by God Almighty, I say the truth and nothing but the truth ; Johan Grimonprez: in conversation with Petra Van Brabandt about Shadow World [2016] ; Sarah Hendrickx: 5 ways to make happier artists
boek